Efficacy of the Dynamic Jaw Mode in Helical Tomotherapy With Static Ports for Breast Cancer. (August 2015) - Sugie, Chikao; Manabe, Yoshihiko; Hayashi, Akihiro; Murai, Taro; Takaoka, Taiki; Hattori, Yukiko; Iwata, Hiromitsu; Takenaka, Ran; Shibamoto, Yuta
The recently developed dynamic jaw technology of tomotherapy can reduce craniocaudal dose spread without much prolonging the treatment time. This study aimed to investigate the efficacy of the dynamic jaw mode for tomotherapy of breast cancer. Static tomotherapy plans of the whole breast and supraclavicular regional lymph nodes, and plans for the whole breast only were generated in 25 patients with left-sided breast cancer. Plans with a field width of 2.5 or 5 cm with the dynamic or fixed jaw modes were made for each patient. The prescribed dose was 50 Gy in 25 fractions. In whole breast and supraclavicular nodal radiotherapy, dose distributions and homogeneity of the planning target volume (PTV) with the dynamic jaw mode were slightly inferior to those with the fixed jaw mode with a 5-cm field width ( P < .05). However, lung low-dose volumes and mean doses of the larynx, thyroid, skin, and all the healthy tissues combined were smaller with the dynamic jaw mode than with the fixed jaw mode with a 5-cm field width ( P < .001). In whole breast radiotherapy, mean doses of the skin and healthy tissues were lower with the dynamic jaw mode than with the fixed jaw mode with a 5-cm field width ( P < .001) without significant differences in PTV dose distributions, homogeneity, and conformity. The dynamic jaw mode provided better sparing of organs at risks with minimal disturbance of dose–volume indices of PTV. Considering the treatment time, the 5-cm-field dynamic jaw mode is more efficient than the 2.5-cm fixed jaw mode.